Centrality of spirituality/religion in the culture of palliative care service in Indonesia: An ethnographic study. (16th January 2018) - Rochmawati, Erna; Wiechula, Rick; Cameron, Kate
Abstract: Experiencing life‐threatening illness could impact on an individual's spirituality or religious beliefs. In this paper, we report on a study which explored cultural elements that influence the provision of palliative care for people with cancer. A contemporary ethnographic approach was adopted. Observations and interviews were undertaken over 3 months with 48 participants, including palliative care staff, patients, and their families. An ethnographic data analysis framework was adopted to assist in the analysis of data at item, pattern, and structural levels. Religion was identified as central to everyday life, with all participants reporting being affiliated to particular religions and performing their religious practices in their daily lives. Patients' relatives acknowledged and addressed patients' needs for these practices. Staff provided spiritual care for the patients and their relatives in the form of religious discussion and conducting prayers together. An understanding that religious and spiritual practices are integral cultural elements and of fundamental importance to the holistic health of their patients is necessary if health‐care professionals are to support patients and their families in end‐of‐life care.